Recuperation of industrial landscapes as cultural landscapes (Ciudades, 2017)
This article attempts to identify the industrial landscape in the theoretical and legal framework of cultural landscapes, -constituted by the main international documents-, to classify  them and within these categories distinguish some significant examples whose analysis allows us to glimpse methodological issues around their assessment processes revealing its  deep significance network and discerning, at the same time, criteria for protection and preservation. These are the industrial landscapes whose activity has ceased and acquire heritage character.They are presented as degraded landscapes, and they are particularly exposed today to a radical transformation and sometimes total disappearance. In this sense, we consider necessary to reflect here around new strategies of interventions, transformations, reuse and also considering their incorporation into the new socio-cultural networks.
Keywords: landscape; heritage; industrial; environmental; conservation; intervention; restoration; reuse